Attosecond spectral singularities in solid-state high-harmonic generation - Uzan, Ayelet Julie; Orenstein, Gal; Bruner, Barry D.; Jimenez-Galan, Álvaro; McDonald, Chris; Silva, Rui E.F.; Klimkin, Nikolai D.; Blanchet, Valerie; Arusi-Parpar, Talya; Krüger, Michael; Rubtsov, Alexey N.; Smirnova, Olga; et al. (Optics InfoBase Conference Papers, 2020)
Using high-harmonic generation spectroscopy, we reveal the underlying attosecond dynamics in multi-band solid-state systems. We identify the mapping of spectral caustics into the high-harmonic spectrum, and probe the structure of multiple unpopulated high conduction bands.
CRIS-Team Scopus Importer:2023-04-20